Studi Apologetika Terhadap Pembuktian Keautentikan Alkitab Menurut 1 Petrus 3:15-16 - Andri Harvijanto (JURNAL ILUMINASI, 2024)
The text of 1 Peter 3:15-16 is often regarded as the foundation for Christian apologetics. However, a deeper analysis within the immediate and broader context of the entire letter of 1 Peter reveals a more complex and diverse meaning than initially perceived. This article aims to thoroughly examine 1 Peter 3:15 and explore its implications and applications for contemporary Christians, taking into account historical, theological, and sociocultural contexts. Through a critical hermeneutical approach, this study hopes to provide new insights that enrich contemporary apologetic practices in addressing the challenges of the present age.